2014
DOI: 10.5005/jp-journals-10024-1607
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Diacetyl Morphine on Salivary Factors and their Changes after Methadone Therapy

Abstract: Heroin addiction changed the effective salivary factors and therefore could negatively contribute to oral health. These factors were not return to the normal range after 1 month of MMT. Physicians should be informed about focusing on oral health in patients under MMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…(16) The results of Akbari's studies showed the rate of oral pigmentation in addicts to be 34.5%, which is consistent with the results of the present study. (12) The prevalence of oral ulcers and herpes was 25% among subjects, which turned out to be similar to that of the O'sullivan's study, which reported a rate of 20% for the incidence of oral ulcers. (9) In the present study, 3% of subjects had leukoplakia, which was quite similar to the results of the Akbari study, with a rate of 4%.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…(16) The results of Akbari's studies showed the rate of oral pigmentation in addicts to be 34.5%, which is consistent with the results of the present study. (12) The prevalence of oral ulcers and herpes was 25% among subjects, which turned out to be similar to that of the O'sullivan's study, which reported a rate of 20% for the incidence of oral ulcers. (9) In the present study, 3% of subjects had leukoplakia, which was quite similar to the results of the Akbari study, with a rate of 4%.…”
Section: Discussionsupporting
confidence: 81%
“…The mean DMFT index was 15.8% in this study, a rate which was 14.4% in O'sullivan's and 16% in Akbari's study. (9,12) The prevalence of dry mouth was 73% in this study, a rate which turned out to be 50% in Ayramloo's research. (13) Dry mouth is an important factor in increasing the incidence of dental caries, periodontal problems and TMD disorders.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Nevertheless, studies comparing heroin users and methadone-treated patients have reported that the MMT group exhibits improvement in redox biomarkers [30, 53, 54]. On the same grounds, TAC is decreased after opioid administration, especially heroin [9, 5557], but it seems that substitutes have a positive effect [9, 58] increasing the antioxidant capacity of the organism. These findings are optimistic because they support the notion that although substitute treatment induces oxidative stress, this occurs in much less extent in comparison to heroin, thus reinforcing its use at rehab programs.…”
Section: Discussionmentioning
confidence: 99%